Model for Ranking the System of Indicators of Node Compromise of Corporate Data Network Nodes - Bezzateev, S. V.; Mylnikov, V. A.; Starodub, A. R. (Automatic control and computer sciences, 2024)
The model of the system of ranking indicators of compromise for active countermeasures against targeted attacks is proposed, which makes it possible to detect threats in advance and plan measures to eliminate them before they manifest themselves. Another important aspect is the development of means and methods for the evaluation of information sources according to their level of confidence for the collection of data necessary for the investigation of incidents. On the basis of the proposed models, an information system for the ranking of compromise indicators was developed in order to minimize the possibility of a breach of the confidentiality, integrity and availability of information, as well as the compromise of data in the system.